DESIGN AND IMPLEMENTATION OF SEPIC CONVERTER FOR NANOSATELLITE APPLICATIONS - AHMAD, MUHAMAD SHUHAIRI (2017)
Modern satellite nowadays come with smaller in size or known as nanosatellite. Nanosatellite is a medium to enhance technology especially in communications and broadcasting areas. Scientist and expert believed using of this nanosatellite advantage in term of its size will bring benefits in the future. are. It is as powerful as current satellite in the outer space. In the nanosatellite architecture, there are various subsystems implemented such as converter circuit, receiver, transmitter, sensor and amplifier. However, designing nanosatellite required advanced technology and knowledges as consider where this nanosatellite will operate in very harsh environment such as exposing to radiation in solar system most of the time at the outer space. In outer space, there are many types of radiation such as gamma radiation. Gamma radiation has capability to penetrate the nanosatellite electrical structures and may cause changes in term of electrical behaviour. This radiation which might able to disturb the performance of nanosatellite as the components who build up the subsystem such as resistor, capacitor and MOSFET reduce in performance or functionality. Therefore, research being carry out to design DC-DC converter by using different MOSFETSs as a switch radiated with 50 krad, 100 krad and 300 krad of gamma radiation intensity. The source of gamma radiation is coming from cobalt-60. DC-DC converter may consist of buck converter, boost converter, buck-boost converter, Cuk converter and Single Ended Primary Inductor Converter or known as SEPIC. SEPIC converter is chosen as it has ability to step up and down the voltage by varying the duty cycles and it also give non-inverting output. This thesis is to demonstrate the simulation results of SEPIC converter through parameters modelling in designing this DC-DC converter. Performance of the SEPIC converter circuit by using radiated and non-radiated MOSFETs at different level of gamma radiation will be compared, analysed and discussed by experimentation procedure.